Kinetics of superoxide ion in dimethyl sulfoxide containing ionic liquids - Hayyan, M.; Hashim, M.A.; AlNashef, I.M. (Springer Verlag (Germany), 2015)
The chemical generation of superoxide ion (O-2 (aEuro cent a')) by dissolving potassium superoxide was investigated. The chemically generated O-2 (aEuro cent a') was then used to study the long-term stability of O-2 (aEuro cent a') in dimethyl sulfoxide (DMSO) containing ionic liquids (ILs) and determine the rate constants based on pseudo 1st- and 2nd-order reactions between the IL and O-2 (aEuro cent a') generated in DMSO. O-2 (aEuro cent a') was unstable in DMSO containing S-222TFSI, DMImMS, BDMImTfO, EMImTFSI, EMImMS, P-14,P-666TPTP, P-14,P-666TFSI, and all pyridinium-based ILs. In contrast, O-2 (aEuro cent a') was very stable in DMSO containing MOPMPipTFSI, BMPyrrDCA, BMPyrrTFSI, BMPyrrTfO, HMPyrrTFSI, MOEMPipTPTP, BMPyrrTFA, N-112,1O(2)TFSI, and MOEMMorTFSI. This shows that these ILs can be used for different applications involving O-2 (aEuro cent a'). The reaction rate constant, total consumption, and consumption rate of O-2 (aEuro cent a') were determined. The rate constants of O-2 (aEuro cent a') in some ILs were found to follow pseudo 1st-order reaction, while in others, pseudo 2nd-order reaction kinetics were observed.